A new conceptual framework for identifying the factors influencing the effectiveness of competitive intelligence. Issue 5 (15th June 2020) - Asghari, Somayeh; Targholi, Sahar; Kazemi, Ali; Shahriyari, Saeed; Rajabion, Lila
Abstract : Purpose: Competitive intelligence (CI) collects data through the distribution of knowledge to make decisions in a competitive environment. To better comprehend the concept of CI, the purpose of this paper is to determine the role of effective factors (knowledge sharing, competitor information, information technology (IT) and organizational culture) and their impact on CI. In addition, the paper provides a conceptual framework for determining the practical factors on CI. Design/methodology/approach: For evaluating the elements of the model, a questionnaire is considered. Questionnaires were reread by specialists with significant experiences in the CI field. For statistical analysis, the SPSS 22 and SmartPLS 3.2 software package is also used. Findings: Findings from the study showed the validity of the model for a CI assessment. Furthermore, the results confirmed that the competitor information significantly influenced CI. In addition, the obtained results implied that IT has a significant and positive influence on CI. The effect of organizational culture on CI also proved to be positive and significant. Research limitations/implications: This paper makes significant contributions for both researchers and practitioners; however, the authors determine some limitations, which are as follows: First, the authors showed the result in a single region. It cannot be assured that the results are generalizable to other areas. Second, because of time and financial constraints, the authors gathered the data using a sample from a single location. Third, the use of variables to depict CI may be not exhaustive. The authors, therefore, encourage future research to study these CI dimensions. Practical implications: This study meaningfully contributes to the knowledge and literature by focusing more on CI, examining other significant aspects and applying advanced statistical analysis method. Also, current research results suggest practical implications for marketing practitioners and managers who implemented tools and made strategic plans to enhance the organization's performance. From a practical perspective, the statistical results support the crucial role of the following factors: IT, competitor information, organizational culture and knowledge sharing on CI. Originality/value: Experts in the area of knowledge management, CI and strategic management can use this study to gain a competitive advantage based on knowledge and information resources. Organizations must have knowledge management function and CI to support the strategy formulation, implementation and evaluation.